THE FEATURES OF EETHNIC IDENTITY IN STUDENTS WITH DUFFERENT TYPES OF RELIGIOSITY - Kuznetsov, O. I. (PSYCHOLOGICAL JOURNAL, 2016)
In the article presents an analysis of the problem of psychological religiosity, its relation to tolerance and ethnic identity. It is proved that high religiosity provides a low tolerance, etnoegoism and etnofanatism. The positive relationships propensity to idealist philosophy and ethnic indifference is shown. Negative attitudes to magic, denying the existence of extraordinary possibilities, belief in witchcraft correlated with indicators of etnonihilism, etnoisolationism. Indicators of religion as a support positively correlated with indicators of positive ethnic identity. External signs of religion in general correspond etnoegoism, etnofanatism and negatively correlated with indicators of ethnic tolerance. Belief in a higher power negatively correlated with etnonihilism and social tolerance, positively correlated with etnoegoism. Interest in pseudoscience provides a high level of etnonihilism, etnoisolationism and social tolerance. Typological features of religiosity among students were determined through characterization obtained typological profiles of religion - low religiosity (the average propensity to idealist philosophy and interest in pseudoscience higher than the average monthly search support in religion, low rates of belief in a higher power or religious identity), moderate religiosity (high rates of susceptibility to idealist philosophy, the average external manifestations of religiosity and religion as a moral example, and low rates of religious identity and other parameters of religiosity), mystical religiosity (high rates of belief in magic and witchcraft, the external manifestations of religion and faith in a higher power) and rational religiosity (high rates found support in religion, interest in pseudoscience, the average for all other indicators of religiosity). Differences in the level of tolerance and ethnic identification depending on the type of religiosity were shown. Moderate level of religiosity characterized etnoegoism the lowest and the highest level of religiosity - the lowest rates of personal tolerance etnonihilism and etnoisolationism.